Clinical impact of red blood cell transfusion on adverse clinical events in acute heart failure patients with anemia. (1st February 2021) - Higuchi, Satoshi; Hata, Noritaka; Shibata, Shigeki; Hirabuki, Kazukuni; Suda, Tomoya; Honda, Kazuna; Hasegawa, Hiroshi; Matsuda, Takeaki
Abstract: Background: Anemia has been recognized as an important comorbidity in patients with acute heart failure (AHF) and is associated with adverse clinical events. However, the clinical impact of red blood cell (RBC) transfusion in such patients is unclear. Method: This study was a retrospective single-center registry including AHF patients admitted to Kyorin University Hospital between 2007 and 2014. Anemia was defined as a hemoglobin level < 130 g/L in males or < 120 g/L in females. Those with major bleeding with a fall in hemoglobin concentration of >20 g/L were excluded. AHF readmission at 3 months and in-hospital and 2-year all-cause mortality were evaluated. Results: Of 501 AHF patients, 38 were excluded owing to major bleeding; finally, 463 (age, 77 ± 11 years; males, 58%) were evaluated. RBC transfusion during hospitalization was performed in 112 patients (24%). Hemoglobin level on admission was 105 ± 16 g/L (transfusion, 89 ± 17 g/L; no transfusion, 110 ± 12 g/L; p  < 0.001). AHF readmission at 3 months and in-hospital and 2-year all-cause mortality were observed in 46 (10%), 16 (3%), and 121 (26%) patients, respectively. Univariate Cox regression analysis demonstrated that RBC transfusion was not associated with AHF readmission at 3 months (hazard ratio: 0.80; 95% confidence interval: 0.39–1.66) The association did not differ at any hemoglobin concentration or left ventricular ejection fraction value. Multivariate Cox regression analysis revealed similar results. Furthermore, RBC transfusion was not correlated with in-hospital and 2-year all-cause mortality. Conclusions: RBC transfusion was not associated with AHF readmission or all-cause mortality. Highlights: Patients with AHF present with various comorbidities, including anemia It has been unclear whether RBC transfusion influences clinical outcomes We studied AHF readmission and all-cause mortality after RBC transfusion RBC transfusion was not associated with either outcome